PM.100 A Rare Case of Anti-NMDA Receptor Encephalitis in Pregnancy. (26th April 2013) - Gaughan, E; Barry, S; McHugh, A; O'Donoghue, F; O'Rourke, K; Lynch, T; McCarthy, A; Sheehan, J; McKenna, P
Abstract : Anti-NMDA receptor encephalitis is a distinct disorder characterised by the predictable sequential development of symptoms; prodromal symptoms are initially noted, followed by prominent psychiatric symptoms, seizures, an unresponsive/catatonic state, hypoventilation, and involuntary orofacial-limb movements. This disorder usually affects young women with ovarian teratoma but may also affect women of any age or even men. We report the case of a 32 year old primigravid woman who developed psychosis with associated catatonia and autonomic dysfunction at 8 weeks gestation. Cranial imaging in the form of CT and MRI was normal. EEG showed slow waves and anti-NMDA receptor encephalitis was suspected. This was confirmed by the finding of serum anti-NMDA antibodies. Transvaginal Ultrasound and pelvic MRI suggested normal ovaries. She required admission to the High Dependency Unit for several weeks but eventually responded to plasma exchange, steroids, azathioprine, Intravenous immunoglobulin and antipsychotics. She had an Emergency LSCS at 32 weeks gestation for PPROM and delivered a healthy male infant. A mature cystic teratoma was found at caesarean section which was excised. Although being rare in pregnancy, anti NMDA encephalitis can respond to aggressive treatment and can be associated with good maternal and fetal outcomes. An awareness of this 'new disease' (first described in 2005) can lead to an occasional but dramatic surgical treatment of a psychotic illness.